Design and development of low cost biceps tendonitis physiotherapy monitoring system using surface EMG electrodes for automated rehabilitation - Poo, Tarn Shi (Universiti Malaysia Perlis (UniMAP), 2019)
Master of Science (Biomedical Electronic Engineering)